2004
DOI: 10.1161/01.cir.0000138386.48852.b6
|View full text |Cite
|
Sign up to set email alerts
|

Growth Rate of Aortic Diameter in Patients With Type B Aortic Dissection During the Chronic Phase

Abstract: Background-The purpose of this study was to evaluate the growth rate of type B double-barrel aortic dissection with computed tomography (CT) and the factors influencing its enlargement. Methods and Results-Sixty-two patients were entered into this study, and regular follow-up CT studies (mean; 49.1 months) were performed. The affected aortas and iliac arteries were divided into 5 segments (aortic arch, descending thoracic, suprarenal abdominal, infrarenal abdominal aorta, and iliac artery). Fifty-two of 62 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(57 citation statements)
references
References 13 publications
2
55
0
Order By: Relevance
“…Endovascular treatment is another option reported to be recommendable especially for its characteristic of thrombus formation in the false lumen. 20) In addition, endovascular treatment can be an effective approach, even for elderly or severely compromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular treatment is another option reported to be recommendable especially for its characteristic of thrombus formation in the false lumen. 20) In addition, endovascular treatment can be an effective approach, even for elderly or severely compromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…202 Conversely, FL thrombosis has been associated with a slower growth rate. 172,173 Interestingly, partial distal FL thrombosis has been shown to be an independent predictor of mortality after hospital discharge in patients with a CTBAD. 174 The responsible mechanism may be increased FL pressure resulting from a large entry tear without outflow.…”
Section: Level Of Evidence Class Recommenda On 29mentioning
confidence: 99%
“…The wide variation of ‰ow velocity and slower helical ‰ow in the dilated lumen may be related to an increase in wall shear stress on the outer wall of the false lumen, which comprises fewer elasticˆbers. 3,19,21,22 In this study, 3 patients with enlarged patent false lumen in the thorax or abdomen showed this type of blood ‰ow patterns, and one patient with a growing ULP had slower helical ‰ow at the ULP. The false lumens with laminar ‰ow or ULPs with stagnant ‰ow did not enlarge in this study.…”
Section: Discussionmentioning
confidence: 52%
“…These results suggest that pathologically helical blood ‰ow, in addition to other risk factors, such as Stanford type, maximum diameter of the aorta, aging, hypertension, and atherosclerosis, may contribute to the deterioration of chronic thoracic aortic dissection. 2,3,5,8,21 This study has also suggested that preemptive surgery might prevent disease progression even in cases of slower helical ‰ow in the false lumen. Further studies with a larger patient population are needed to conˆrm these preliminary results.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation